Parity Quantum Optimization: Encoding Constraints - Maike Drieb-Schön; Kilian Ender; Younes Javanmard; Wolfgang Lechner (Quantum, 2023)
Constraints make hard optimization problems even harder to solve on quantum devices because they are implemented with large energy penalties and additional qubit overhead. The parity mapping, which has been introduced as an alternative to the spin encoding, translates the problem to a representation using only parity variables that encodes products of spin variables. In combining exchange interaction and single spin flip terms in the parity representation, constraints on sums and products of arbitrary $k$-body terms can be implemented without additional overhead in two-dimensional quantum systems.